Peripheral ameloblastoma of the gingiva - Nagaraja Vezhavendhan; Santhanam Vidyalakshmi; Rajakannu Muthukumaran; Arumugam Santhadevy; Muthanandam Sivaramakrishnan; Chandrasekar Gayathri (University of São Paulo, 2020)
Peripheral Ameloblastoma (PA) is a benign odontogenic tumor, arising from the cell rest of Serres, reduced enamel epithelium and basal cells of the surface epithelium. Peripheral ameloblastoma is a rare odontogenic neoplasm occurring commonly in the mandibular gingiva. PA clinically resembles other peripherally occurring lesions like pyogenic granuloma, peripheral ossifying fibroma, peripheral giant cell granuloma, and squamous papilloma. The recurrence rate of PA is 16-19% which demands a straight follow up. We report a case of recurrent peripheral ameloblastoma occurring in a 72-year old male located in the mandibular lingual gingiva in relation to the 44, 45 element's regions. The patient had a primary lesion excised from the same site 6 years before which was diagnosed as ameloblastoma.